PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Fisika Pokok Bahasan Hukum Newton Siswa Kelas X MIPA SMA Negeri 3 Pagar Alam) - Hermala Hermala; Johanes Sapri (UNIB Press, 2021)
This research aims to describe the application of the discovery leaming model to improve solving skills. problems, student achievement, application of discovery leaming models to improve student achievement. This research uses Classroom Action Research followed by a quasi experiment. The research subjects were 36 students of class X MIPA1, the even semester of the 2020/2021 school year of SMA Negeri 3 Pagar Alam. The sample for the quasi-experimental class was X MIPA2 totaling 36 students, and the control class was X MIPA3 totaling 36 students. Data collection techniques used observation sheets and learning achievement tests, while data analysis used the mean and t test. The results of this study concluded that the application of the discovery learning model can improve the problem-solving ability and student achievement, as well as effectively improve the learning achievement of class X MIPA students at SMA Negeri 3 Pagar Alam. and describe the effectiveness.